ADMINISTRATIVE DEFERENCE AND ITS LINK WITH THE NON-DELEGATION DOCTRINE IN THE LAW OF THE UNITED STATES - DOI 10.5935/2448-0517.20200036 - Di Gioia, Ilaria (Juris Poiesis - Qualis A3, 2020)
This essay is an exploration of the theoretical origins of administrative deference in the Unites States. It argues that the doctrine of administrative deference finds its theoretical justification in the increasing delegation of the power to execute statutes from Congress to the Executive. It discusses the cases of Chevron and Mead as key cases for the evolution of the delegation doctrine and concludes with the recent treatment of the doctrine in the case of Gundy.